Supplementation of Soil with Waste Sulfur and Its Effect on Availability of Mn and Zn - Aneta Lisowska; Barbara Filipek-Mazur; Andrzej Kalisz; Zofia Gródek-Szostak; Agnieszka Kowalczyk (Agronomy, 2022)
Sulfur is a necessary nutrient for the proper functioning of living organisms, both plants and animals. However, following pro-environmental activities carried out for many years, there is now a deficit of this element in the soils of many countries. The aim of this model study was to determine the effect of the application of waste elemental sulfur and its mixtures with organic materials (cattle manure, digestate and biochar) on the availability of manganese and zinc in soils. In addition to the standard analysis of variance (ANOVA), the authors propose various methods of advanced statistical analysis, e.g., simplified linear or polynomial regression model development, multiple regression analysis, heatmap statistics and principal component analysis (PCA). The presented findings indicate significant relationships between the soil pH value, S-SO4, Zn and Mn contents, dehydrogenase activity, and experimental duration. The results of regression analysis revealed that the applied materials had a more significant influence on the zinc content than on the manganese content during the incubation period.